HUBUNGAN PENGETAHUAN PERAWAT DENGAN KEPATUHAN PENGISIAN EARLY WARNING SCORING SYSTEM (EWSS) DI RUANG RAWAT INAP RUMAH SAKIT SANTA ELISABETH BATAM KOTA TAHUN 2022 - Jagentar Pane; Rotua Elvina Pakpahan; Lindawati F. Tampubolon; Erbin Landong Sirait (Jurnal Cakrawala Ilmiah, 2024)
Background: One strategy to reduce cardiac arrest deaths is to implement an Early Warning Score System (EWSS). EWSS is a method of early detection of decreased physiological condition of patients with six parameters, namely systolic blood pressure, pulse, breathing, body temperature, oxygen saturation, and awareness level based on the results of the score assessment assessment so that interventions can be carried out in accordance with the results of the study. Research Objectives: This study aims to determine the Relationship between Nurse Knowledge and Compliance with the Early Warning Scoring System (EWSS) in the Inpatient Room of Santa Elisabeth Hospital, Batam City in 2022. Method: This study is a correlation study with cross-sectional design. The population in this study was all nurses in the treatment room of Santa Elisabeth Hospital Batam City, as many as 91 people. Sampling using non probability method with puposive sampling technique. The sample in the study was 73 nurses. The analysis was performed by univariate and bivariate methods using the computerized sistem program. Result: H's knowledge of nurses who are in accordance with the filling of the Early Warning Score System (EWSS) at Santa Elisabeth Hospital Batam Kota was measured using the Pearson correlation test, and the results of the correlation coefficient (r) between nurse knowledge and compliance with the filling system were obtained The Early Warning Score (EWSS) is 0.919 and an interpretation value with a strong relationship is obtained. The results of the analysis of the two variables have a significance value of P = <0.001. Conclusion: Based on the results of the study, it can be concluded that there is a meaningful relationship between the relationship between nurse knowledge and EWSS filling compliance in the sense that the better the knowledge the nurse has, the more obedient it will be in filling out the Early Warning Score System (EWSS) at Santa Elisabeth Hospital in Batam City.